AB0347 Body composition in patients with rheumatoid arthritis kazakh nationality. (12th June 2018) - Gabdulina, G.; Tokarev, A.; Mussabaeva, D.
Abstract : Background: Chronic inflammation in rheumatoid arthritis (RA) leads to a decrease in fat and muscle mass [Baker J.F., Von Feldt J. Mostoufi-Moab S. et al., 2014 Low muscle mass in RA is considered as the main criterion of sarcopenia. Recently, much attention has been paid to various phenotypes of sarcopenia, among which osteopenic sarcopenia, sarcopenic obesity and osteosarcopic obesity (most unfavourable in terms of functional disorders) are distinguished. In the modern literature there are works devoted to changes in the composition of the body in the aspect of abdominal obesity and its influence on cardiovascular risk in RA [Crowson C.S., Myasoedova E., Davis J.M., 2011). Studies with the evaluation of muscle mass and sarcopenia in RA are few. In Kazakhstan, the composition of the human body was not studied. Objectives: The purpose of the study was to study the body composition (muscle and fat mass) of patients with RA of Kazakh nationality using bioelectrical impedance analysis. Methods: In our study we used Bioimpedance analyzer 101 (BIA 101, Italy). Bioimpedansometry was performed in 585 participants, including 295 patients with RA and 290 of their siblings. Results: In patients with RA, in contrast to the comparison group (sibs), BMI (probands – 25.34±5.1, siblings – 24.86±4.45), the girth of the waist and hips were slightly higher than those of the siblings. The ratio of RT/OB in both groups was virtually the same. At the same time, a decrease in the lean mass was found (probands – 45.37±12.2, siblings – 48.67±11.01), which, in all probability, is due to sarcopenia. The presence of sarcopenia is also confirmed by a decrease in the sarcopenia index (probands 0.6884±0.1, sibs 0.6947±0.1). On the contrary, the fat content of RA patients is higher than that of siblings. Conclusions: Thus, in our patients cachexia is formed in RA, which is characterised by loss of muscle mass with the preservation or even growth of fat mass, which stabilises body mass indexes, and in some cases even leads to its increase (so-called cachexial obesity). References: [1] Baker JF, Von Feldt J, Mostoufi-Moab S, et al. Deficits in muscle mass, muscle density, and modified associations with fat in rheumatoid arthritis. Arthritis Care Res (Hoboken)2014;66(11):1612–18. [2] Crowson CS, Myasoedova E, Davis JM 3rd, et al. Increased prevalence of metabolic syndrome associated with rheumatoid arthritis in patients without clinical cardiovascular disease. J Rheumatol2011;38(1):29–35. Disclosure of Interest: None declared